2021
DOI: 10.3889/oamjms.2021.6249
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Model for Orphan’s Emotional and Behavioral Problems: A Scoping Review

Abstract: BACKGROUND: As many as, 45% of orphaned children and adolescents living in orphanages experience behavioral and emotional problems. Several literature reviews on the intervention of emotional and behavioral problems in orphan children and adolescents have been widely conducted. However, there is paucity in the reviews of emotional and behavioral problem interventions in the orphan group based on the type of group approach used in published articles. AIM: This study aimed to synthesize the results on the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…It has been reported that orphanage caregivers are typically under stress and exhausted, due to workload and lack of context-specific training in child development and management of children's emotional and behavioural issues (Furlong et al, 2012;Khalid et al, 2022a). Findings corroborate that maltreatment by caregivers in institutional settings is associated with job-related stress, primarily attributed to a lack of caregiving knowledge and skills (Çatay & Kolo glugil, 2017;Hermenau et al, 2015;Isnaeni et al, 2021). In a study with caregivers in Ukrainian orphanages, Raskin et al (2015) found that caregivers' job-related stress negatively affected both work motivation and child development.…”
Section: Introductionmentioning
confidence: 69%
“…It has been reported that orphanage caregivers are typically under stress and exhausted, due to workload and lack of context-specific training in child development and management of children's emotional and behavioural issues (Furlong et al, 2012;Khalid et al, 2022a). Findings corroborate that maltreatment by caregivers in institutional settings is associated with job-related stress, primarily attributed to a lack of caregiving knowledge and skills (Çatay & Kolo glugil, 2017;Hermenau et al, 2015;Isnaeni et al, 2021). In a study with caregivers in Ukrainian orphanages, Raskin et al (2015) found that caregivers' job-related stress negatively affected both work motivation and child development.…”
Section: Introductionmentioning
confidence: 69%
“…Anak-anak yatim piatu remaja sering kali mendapatkan dampak negatif akibat tidak memadainya perawatan yang diberikan oleh wali di panti asuhan (Disassa and Lamessa, 2021). Isnaeni et al, (2021) menemukan bahwa permasalahan emosi dan perilaku yang paling banyak dihadapi oleh remaja yatim piatu adalah rasa cemas, putus asa, dan rendah diri, diikuti perasaan trauma, marah, dan depresi. Dibandingkan dengan remaja yang bukan yatim piatu yang masih mempunyai kesempatan untuk mendapatkan kasih sayang, cinta, dan perhatian dari orang tuanya, keadaan tersebut menyebabkan remaja yatim piatu mengalami gangguan emosional seperti depresi, kecemasan, dan stres (Deutsch et al, 2015) Sebagai bentuk dari tindakan pencegahan serta pengobatan bagi anak-anak yang mengalami gangguan kesehatan mental diperlukan pendampingan serta pelaksanaan program konseling.…”
Section: Hasilunclassified

Kajian Kesehatan Mental pada Anak-Anak Yatim Piatu

Indra Praekanata,
Komang Sri Yuliastini,
Florina Laurence Zagoto
et al. 2023
pelitapaud
“…Higher quality caregiver–child relationships are associated with better outcomes in children's psychological growth and development (Begle et al, 2010 ; Black et al, 2001 ; Dubowitz et al, 2011 ; Huynh et al, 2019 ; Warner et al, 2017 ). Many recent studies in orphanages also reported positive effects of context‐specific interventions and staff training that helped to create a warm caregiving environment built on the basic principles of at‐home care, supported positive relationships and quality interactions between caregivers and children and enhanced developmental outcomes in orphaned children (Berument, 2013 ; Ghera et al, 2009 ; Isnaeni et al, 2021 ; Kaur et al, 2018 ; Mohammadzadeh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%